(untitled) (Journal of the College of Basic Education, 2023)
Throughout many years of teaching English at all university levels and proof reading of so many theses and dissertations, the researchers feel the Iraqi postgraduate students’ need for an extensive course in English. This would help them get rid of many common errors they make when writing English. Such a course should consider types and causes of the errors made, and contribute in illuminating them. Besides experience, the researchers have checked fifteen theses on Scientific specialization, and the most common errors have been classified, described, and explained so as both teachers and students may focus on them for the sake of a better command of the English language.